Theorizing from the Literature: Rural NC African American Males Who Fail to Complete Early College - Joyce B Valentine (Adult Education Research Conference, 2016)
The African American male dropout rate remains horrific. Educational institutions need to revise their curriculum design and retention strategies. This study examines rural African American males who fail to complete high school using intersectionality and ecological systems theory.
Keywords: Rural African American males; Early College High Schools; intersectionality; ecological systems theory